Designing Single Polymer Molecules as Gas Hydrate and Corrosion Inhibitors - Sheng, Qi (Curtin University, 2018)
This study aims to develop next generation kinetic hydrate and corrosion inhibitors (KHCIs) for the oil and gas industry. Libraries of polymers with specific architectures were designed, synthesized and tested with both targets in mind. For this purpose, an innovative high-throughput hydrate screening method was developed and applied for the first screening tests. This study describes a systematic method for synthesizing and screening newly developed multifunctional inhibitors for both hydrate- and corrosion inhibition.